GAYA GAYA BAHASA SINDIRAN DALAM KANAL YOUTUBE ACARA “LAPOR PAK” TRANS 7 - Peby Dwi Alita Peby; Alber (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The satirical language style is now often used in Indonesian comedy shows, especially television shows, comedians often use satirical language style to satirize politicians, fellow artists, or even the common people. It is intended that the social problems that occur can activate human consciousness itself. With this research, readers will not only get the humorous side, but also be able to find out the various types and meanings contained in satire throws. The method used in this research is content analysis method or content analysis. This research describes or describes what is the problem, then analyzes and interprets the existing data. The object to be explored is the five types of satire and criticism uttered by the cast of the Report Pak program using data from sentences containing satire and criticism. From the data obtained, there are 5 types of satirical language studied by the author. The language of satire is irony, cynicism, sarcasm, satire and innuendo. The data obtained by the author amounted to 24 data consisting of 2 styles of irony satire, 14 data of cynicism, 5 of sarcasm, 2 of satire and 1 of innuendo. So of the five types of satire language, the one most often used by Lapor Pak players is the satire language style of cynicism, while the least used is the satire innuendo language style, this is because with the satirical language of cynicism the expressions raised can become awareness for listeners in critical thing. Keywords: Language style, Insinuation, Event report sir.